KOMUNIKASI PERSUASIF MENURUT AL-QURAN - Muh. Ilyas (AL TAJDID, 2010)
The paradox realities between the splendor of Islamic preaching recently and the spread of evils indicate that the implementation of islamic preaching is separated from the social realities. Among of the efforts to overcome to this problem is “re-reading” the qur’anic doctrines of Islamic Preaching (dakwah), and integrating them with social sciences especially science of communication. Among of the results of that combining is “persuasive preaching”, that is dakwah with persuasive communication approach. Persuasive preaching is preaching based on the principles of effective communication. Effective communication is communication based on audiences’ (mad’u) needs and gratifications whose different frame of references and field of experiences.